Mosquito fauna (Diptera: Culicidae) in phytotelmata environments of the Guapiaçu Ecological Reserve, Cachoeiras de Macacu, Rio de Janeiro, Brazil - de Almeida, Nathália Menezes; Dias, Rayane Ferreira; Alves, Dálete Cássia Vieira; Machado, Sergio Lisboa; Silva, Júlia dos Santos; de Mello, Cecilia Ferreira; Alencar, Jeronimo (Frontiers in Ecology and Evolution, 2025)
IntroductionPhytotelmata are plant structures that collect and retain water, serving as natural larval habitats. Certain species of culicids utilize these water-holding structures for larval development, playing a crucial role in water retention and nutriente cycling, which benefits resident fauna in tropical forests, such as the Atlantic Forest. This study aimed to characterize the taxonomic composition, diversity, species richness, and abundance of mosquitoes within three types of phytotelmata in an Atlantic Forest remnant.MethodsMonthly monitoring of mosquito populations was conducted over one year, from March 2023 to February 2024, considering abiotic factors such as temperature, pH, and rainfall, which can influence mosquito larval growth and abundance. Sampling occurred in selected phytotelm habitats along trails within the study area.ResultsA total of 2,672 culicid specimens were collected, representing 11 genera and 29 species. The most abundant species were Wyeomyia artrostigma, Culex pleuristriatus, and Onirion personatum. Bamboo internodes yielded the highest abundance of specimens (67.4%), followed by bromeliads (30.7%) and buttress roots (1.9%). This distribution pattern may be due to the varying suitability of diferente phytotelmata as larval habitats, with bamboo internodes providing more favorable environmental conditions for larval survival. Among types of phytotelmata, bamboo internodes had the highest species richness (22 species) and the largest total number of specimens, highlighting this habitat’s importance for the development of many mosquito species. In contrast, buttress roots, despite having fewer specimens, showed the greatest diversity and evenness, indicating a balanced species distribution within this habitat. Kruskal-Wallis analysis revealed significant differences in species abundance among the types of phytotelmata evaluated, suggesting that mosquito population composition and abundance are habitat-dependent.DiscussionThese results support the idea that different phytotelmata offer distinct ecological conditions, influencing the occurrence and development of culicid populations. Notable among the species collected were Aedes albopictus and Haemagogus leucocelaenus, known vectors of human pathogens. This study provides valuable insights into the mosquito fauna associated with phytotelmata in an Atlantic Forest remnant, contributing to our understanding of the diversity and ecological dynamics of these environments. Our findings also have public health implications, demonstrating the presence of vector species in a natural habitat, which could inform future research and disease control strategies.